An Improvised Methodology to Unbar Android Mobile Phone for Forensic Examination - V. Balajichandrasekhar M.; T. Srinivasa Rao; G. Srinivas (Institute of Advanced Engineering and Science, 2018)
At the end of 2015, there were 4.7 billion noteworthy mobile subscribers globally, equivalent to 63% of the world’s population. Mobile phones had all the essential components or characteristics neatly fitted into a small space and designed to achieve high speeds, massive storage, and increased functionalities. Smart phones used to carry out imparting or exchanging of information such as calling, texting, Internet browsing, e-mail, photos, videos, and etc. Criminals can use smart phones for a number of activities. Namely, committing a fraud over e-mail, harassment via text messages, drug trafficking, child pornography, etc. In this research paper, We demonstrate, if a mobile phone is identified in a criminal activity and if it is locked by any one of the locking mechanisms such as pattern lock, PIN lock and password lock, then how to unlock the mobile device without data loss for forensic examination. It is a great challenge for forensic experts to extract data from a mobile phone for forensic purpose that can be used as evidence in the court of law. The experimental results show that our approach can break all kinds of pattern locks.